Glymphatic system dysfunction in children with autism spectrum disorder as evidenced by the diffusion tensor imaging along perivascular spaces index - Zhao, Shengnan; Zhang, Manxue; Luo, Tingting; Li, Lei; Jiang, Yuchu; Situ, Mingjing; Huang, Yi (Frontiers in Psychiatry, 2025)
IntroductionThis study aims to evaluate glymphatic system function in autism spectrum disorder (ASD) by employing diffusion tensor imaging along perivascular spaces (DTI-ALPS), and investigate its relationship with visual-motor integration (VMI) function.Materials and methodsA total of 78 individuals with ASD and 48 typically developing (TD) children were enrolled. All participants underwent diffusion tensor imaging on a 3-T MRI scanner. The DTI-ALPS index was calculated, and data on IQ and VMI function were obtained. Independent-samples t-test was used to compare the DTI-ALPS index between groups. Correlation analysis was conducted to examine the relationships between the DTI-ALPS index and clinical variables, including core symptoms, within the ASD group. Mediation analysis explored the relationship among the DTI-ALPS index, core symptoms, and VMI function.ResultsCompared to the TD group, ASD patients showed significantly reduced DTI-ALPS indices in the left hemisphere (DTI-ALPS-L), right hemisphere (DTI-ALPS-R), and for the whole-brain mean (Mean DTI-ALPS). In the ASD group, these indices were negatively correlated with the Autism Diagnostic Interview-Revised (ADI_R) communication score but positively correlated to the VMI score. Mediation analysis revealed that the VMI score significantly mediated the relationship between DTI-ALPS-R and the ADI_R communication score (indirect effect β = -0.082, p< 0.001).ConclusionsOur preliminary findings indicate impaired glymphatic system function in ASD, which may contribute to its pathogenesis. Furthermore, VMI function mediates the relationship between altered glymphatic system function and communication deficits in ASD.